DESIGN OF THE MU DIABETES APPLICATION AS AN EDUCATIONAL METHOD OF TYPE II DIABETES MELLITUS BASED ON ANDROID SOFTWARE - Isma Fajriati; Iis Siti Nurhasanah; Nurhidayati Harun; Nia Kurniasih; Susan Sintia Ramdani (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2024)
Diabetes mellitus is a chronic condition prevalent among individuals. The cornerstone of effective diabetes management is strict adherence to daily medication intake. Deviation from the prescribed medication regimen poses a substantial risk of exacerbating disease and precipitating complications. Recognizing the necessity for educational interventions to bolster medication adherence among individuals with diabetes mellitus, the Mu Diabetes application was developed using the Android software. This research endeavors to devise an application encompassing comprehensive education on type II diabetes mellitus treatment with the primary aim of enhancing medication adherence. Employing a research and development approach, the study entailed designing, coding, and testing the application using the waterfall method and System Usability Scale questionnaire methodology, respectively. The resultant Android-based Mu Diabetes application, as evidenced by the trial outcomes using a Likert scale, yielded an average score of 80. In summary, the findings affirm the feasibility and utility of the Mu Diabetes application as a viable tool for managing type II diabetes mellitus and promoting medication adherence. Keywords: DM Type II, Drugs, android, application, alarm